2021
DOI: 10.1007/s10072-021-05690-5
|View full text |Cite
|
Sign up to set email alerts
|

Intrathecal therapy for tuberculous meningitis: propensity-matched cohort study

Abstract: ObjectiveThe study aimed to determine the safety and efficacy of intrathecally administered isoniazid (INH) and prednisolone in addition to systemic anti-TB therapy and compare it with systemic anti-TB therapy alone in adult patients with tuberculous meningitis (TBM). Methods In this retrospective study, patients were categorized into two groups: Group A patients received systematic anti-TB therapy alone, Group B patients received IT INH (50 mg) and prednisolone (25 mg) twice a week together with the same stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Furthermore, the OR for poor outcomes was 0.386 (95% CI: 0.136–1.094; p = 0.073), suggesting a trend towards improved outcomes in the IT therapy group, although statistical significance was not reached. These findings underscore the potential benefit of incorporating IT therapy with systemic anti-TB in the management of TBM, particularly in reducing mortality rates [ 124 ].…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Furthermore, the OR for poor outcomes was 0.386 (95% CI: 0.136–1.094; p = 0.073), suggesting a trend towards improved outcomes in the IT therapy group, although statistical significance was not reached. These findings underscore the potential benefit of incorporating IT therapy with systemic anti-TB in the management of TBM, particularly in reducing mortality rates [ 124 ].…”
Section: Resultsmentioning
confidence: 96%
“…Comparing IT-INH alongside systemic therapy vs. systemic INH alone: A propensity-matched cohort study compared IT-INH alongside systemic therapy to systemic anti-TB therapy alone, highlighting the advantages of the concomitant treatment approach. This study showed that integrating IT therapy with systemic anti-TB therapy was more effective than systemic therapy alone in patients with TBM over long-term follow-up [ 124 ]. In the overall cohort, there were 36 patients in the IT group and 162 patients in the systemic therapy group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The combination of intrathecal administration of isoniazid and prednisolone has been reported to be associated with a reduced mortality rate ( 7 ), although little is known about its efficacy. Intrathecal treatment for tuberculous meningitis is not mentioned in any of the major guidelines, and treatments are not yet standardized.…”
Section: Discussionmentioning
confidence: 99%
“…In patients treated with intrathecal hydrocortisone, survival rates were much higher, disease duration was much shorter, coma and hospital stay were much shorter, and sequelae were much less severe. Li K [ 33 ] et al conducted a retrospective study on adult patients. Patients in Group A received only systemic antituberculosis treatment, while patients in Group B received twice-weekly intrathecal isoniazid (50 mg) and prednisolone (25 mg) in addition to systemic antituberculosis treatment.198 patients with TBM were included in a total of 60 cases for comparison through propensity score matching, with 30 cases in each group.…”
Section: Pharmacokinetics Of It-gcmentioning
confidence: 99%